Prophylactic Desexualizing Mastectomy for an Intellectually Disabled Woman: Protective Measure or Disregard for Autonomy? - Omar Allam, MD; Emily Gudbranson, BA; Aaron S. Long, BS; Michael Alperovich, MD, MSc; Tomer Avraham, MD (Plastic and Reconstructive Surgery, Global Open, 2022)
Summary:. Historically, sterilization of the so-called feeble-minded has been advocated in the name of eugenics. Surrogate decision-making that impacts sexuality of the intellectually disabled presents significant ethical dilemmas. We describe a 19-year-old intellectually disabled woman who presented with her legal decision-maker for surgical correction of her asymmetric chest and hypoplastic breast. The decision-maker requested a mastectomy to make the patient’s breasts as inconspicuous as possible, and to reduce the risk of sexual assault and pregnancy. This case covers the ethical considerations on whether or not to prophylactically desexualize an intellectually disabled woman.